Організація академічно-громадського навчання як складова професійної підготовки студентів у системі університетської освіти США - Ореста Клонцак (Pavlo Tychyna Uman State Pedagogical University, 2015)
Розглянуто поняття професійної підготовки студентів як невід'ємної складової університетської освіти. Розкрито суть поняття «академічно-громадське навчання» як складової професійної підготовки студентів у системі університетської освіти США. Представлено модель організації академічно-громадського навчання, розроблену американськими вченими на базі Університету Пердью в Індіанаполісі, штат Індіана. Продемонстровано модель експериментального навчання Д. А. Кольба, яка лежить в основі академічно-громадського навчання. На підставі теоретико-емпіричних досліджень проаналізовано шляхи організації академічно-громадського навчання в системі університетської освіти США. Зосереджено увагу на реф-лексії як ключовому елементі організації академічно-громадського навчання. Рассмотрено понятие профессиональной подготовки студентов как неотъемлемой составляющей университетского образования. Раскрыта суть понятия академически общественного обучения как составляющей профессиональной подготовки студентов в системе университетского образования США. Представлена модель организации академии-чески общественного обучения, разработанную учеными на базе Университета Пердью в Индианаполисе, штат Индиана. Продемонстрирована модель экспериментального обучения Кольба Д. А., которая лежит в основе академически общественного обучения. На основании теоретико-эмпирических исследований проанализированы пути организации академически общественного обучения в системе университетского образования США. Сосредоточено внимание на рефлексии как ключевом элементе организации академически общественного обучения. The article is devoted to the organization of academic service-learning in the university system of the USA. The main task of university education is students' professional training. Students should be taught to think critically, and make their own professional decisions. The notion of students' professional training as an integral part of the university education is examined. The essence of the concept of academic service-learning as a part of students' professional training in the system of university education of the USA is studied. Academic service-learning can be regarded as extracurricular or curricular activity. Curricular service-learning is defined as educational strategy that involves students to public activities in order to meet the needs of the community, and to help students better understand the content of the curriculum or discipline, and to enhance the sense of public responsibility. The model of organization of academic service-learning developed by scientists at the Purdue University in Indianapolis, Indiana is demonstrated. Service-learning at the institutional level can be characterized as a cycle that includes awareness, planning, prototype, support, expansion, and evaluation. The model of experiential learning developed by Kolb D.A. as the basis of academic service-learning is demonstrated. It includes abstract conceptualization, active experimentation, concrete experience, reflective observation. Based on theoretical and empirical studies the ways of organization of academic service-learning in the system of university education of the USA are analyzed. The author pays attention to reflection as a key element of academic service-learning. Reflective activities are characterized by the following features: link experience to learning; are guided; occur regularly; allow feedback and assessment; foster the exploration and clarification of values. Positive impact of academic service-learning to students' professional training in the system of university education of the USA is shown.